2004
DOI: 10.2343/geochemj.38.515
|View full text |Cite
|
Sign up to set email alerts
|

La/Yb and Th/Sc in settling particles: Vertical and horizontal transport of lithogenic material in the western North Pacific

Abstract: In order to understand the origins and transport processes of lithogenic aluminosilicate in the western North Pacific, time-series sediment traps were deployed at Stn. KNOT at 44∞N 155∞E (water depth: 5320 m). Annual mean content of aluminum (Al) which is a proxy of lithogenic material in settling particles was 0.38% at 1 km depth, 0.78% at 3 km depth and 1.14% at 5 km depth, respectively. Mass fluxes were corrected by 230 Th and 231 Pa activities in particles and seawater. Annual mean corrected Al fluxes at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 56 publications
2
18
0
Order By: Relevance
“…A major source is volcanic ash from the surrounding Kurile, Aleutian, Kamchatka, Alaska and Japan volcanic arcs (Bailey, 1993;Jones et al, 1994Jones et al, , 2000Maeda et al, 2007;Nakai et al, 1993;Olivarez et al, 1991;Otosaka et al, 2004;Shigemitsu et al, 2007;Weber et al, 1996). Also contributing to the lithogenic fraction are hemipelagic material (Jones et al, 1994(Jones et al, , 2000, ice-rafted debris (IRD;McKelvey et al, 1995;St.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A major source is volcanic ash from the surrounding Kurile, Aleutian, Kamchatka, Alaska and Japan volcanic arcs (Bailey, 1993;Jones et al, 1994Jones et al, , 2000Maeda et al, 2007;Nakai et al, 1993;Olivarez et al, 1991;Otosaka et al, 2004;Shigemitsu et al, 2007;Weber et al, 1996). Also contributing to the lithogenic fraction are hemipelagic material (Jones et al, 1994(Jones et al, , 2000, ice-rafted debris (IRD;McKelvey et al, 1995;St.…”
Section: Discussionmentioning
confidence: 99%
“…3, 4). As the surrounding land is of volcanic origin, the hemipelagic and riverine input as well as IRD have a geochemical signature similar to the fine-grained volcanic ash (Jones et al, 1994;McKelvey et al, 1995;Otosaka et al, 2004;Shigemitsu et al, 2007) and are therefore accounted for by the volcanic endmembers.…”
Section: Deconvolution Of Lithogenic Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…based on mineralogy (Griffin et al, 1968), the isotopic composition of neodymium and strontium (Nakai et al, 1993;Jones et al, 1994), and the elemental composition of sediment and settling particles (Weber et al, 1996;Otosaka and Noriki, 2000;Otosaka et al, 2004). These studies revealed that the source materials of lithogenic particles in sediment and settling particles in the north Pacific are Asian loess and volcanic materials from the Kurile-Kamchatka Islands.…”
mentioning
confidence: 99%
“…The behavior of settling lithogenic particles in the ocean has been studied using sediment traps (e.g., Honjo et al, 1982;Walsh et al, 1988;Saito et al, 1992;Otosaka et al, 2004). Previous studies have concluded that lithogenic particle fluxes increase with depth and that the increases were caused by laterally transported particles.…”
mentioning
confidence: 99%